Inhibitory Test of Sweet Potato Leaves Infusion (Impomea batatas L.) Toward the Growth of (Propeniumbacterium acnes) - Zulfiah Zulfiah; Megawati Megawati; Herman Herman; Sulfiyana H. Ambo Lau; Muhammad Farid Hasyim; Murniati Murniati; Sainal Edi Kamal; Yuniharce Kadang; Nurul Izza AR.; Gerfan Patandung; Alfreds Roosevelt (Jurnal Farmasi Sandi Karsa, 2021)
The research of sweet potato leaf infusion has been done. Based on statistical analysis and discussing of the result of the research. It has been concluded that sweet potato leaves infusion (Ipomoea batatas L.) by using diffusion method, significantly hinder the growth of bacteria (propionibacterium acnes with optimum inhibition zone namely positive control and strong effectiveness. This research was done in july to august 2019 in microbiology laboratories Pharmacy Academy of Sandi Karsa Makassar. The aim of this research is to know the test of sweet potato leaves infusion activities in obstructing the growth of Propionibacterium acnes. The result of this research has shown that the sweet potato leaves infusion Ipomoea batatas) on concentration 5%, 10% and 15% has a zone of inhibition.